Supplemental Watermelon Juice Attenuates Acute Hyperglycemia-Induced Macro-and Microvascular Dysfunction in Healthy Adults. Issue 11 (11th September 2021) - Vincellette, Cullen M; Losso, Jack; Early, Kate; Spielmann, Guillaume; Irving, Brian A; Allerton, Timothy D
ABSTRACT: Background: Acute hyperglycemia reduces NO bioavailability and causes macro- and microvascular dysfunction. Watermelon juice (WMJ) is a natural source of the amino acid citrulline, which is metabolized to form arginine for the NO cycle and may improve vascular function. Objectives: We examined the effects of 2 weeks of WMJ compared to a calorie-matched placebo (PLA) to attenuate acute hyperglycemia-induced vascular dysfunction. Methods: In a randomized, placebo-controlled, double-blind, crossover trial, 6 men and 11 women (aged 21–25; BMI, 23.5 ± 3.2 kg/m 2 ) received 2 weeks of daily WMJ (500 mL) or a PLA drink followed by an oral-glucose-tolerance test. Postprandial flow-mediated dilation (FMD) was measured by ultrasound (primary outcome), while postprandial microvascular blood flow (MVBF) and ischemic reperfusion were measured by near-infrared spectroscopy (NIRS) vascular occlusion test (VOT). Results: The postprandial FMD area AUC was higher after WMJ supplementation compared to PLA supplementation (838 ± 459% · 90 min compared with 539 ± 278% · 90 min; P = 0.03). The postprandial MVBF (AUC) was higher ( P = 0.01) following WMJ supplementation (51.0 ± 29.1 mL blood · 100 mL tissue –1 · min –1 · 90 min) compared to the PLA (36.0 ± 20.5 mL blood · 100 mL tissue –1 · min –1 · 90 min; P = 0.01). There was a significant treatment effect ( P = 0.048) for WMJ supplementation (71.2 ± 1.5%) to increase baseline tissue oxygen saturation (StO2 %) when compared to PLA (65.9 ± 1.7%). The ischemic-reperfusion slope was not affected by WMJ treatment ( P = 0.83). Conclusions: Two weeks of daily WMJ supplementation improved FMD and some aspects of microvascular function (NIRS-VOT) during experimentally induced acute hyperglycemia in healthy adults. Preserved postprandial endothelial function and enhanced skeletal muscle StO2 % are likely partially mediated by increased NO production (via citrulline conversion into arginine) and by the potential antioxidant effect of other bioactive compounds in WMJ.